The First Blockchain: Bitcoin, Entropy, Religion. - Damour, Frank (Zygon: Journal of Religion & Science, 2024)
Bitcoin did not suddenly appear in November 2008, at the heart of the subprime crisis. It has matured over a decade, notably through the exchanges of Nick Szabo, Hal Finney, and others, with key moments such as the publication of "The God Protocols" by Szabo in 1997. The theological analogy developed in the introduction to that text, which theorizes smart contracts, raises the question: simple facetiousness, geek irony, or a clue to religious references? By analysing not only the founding texts but also the discussions in the Extropian or cryptography mailing lists in which Szabo and Finney took part, this article seeks to answer whether religious references (vocabulary, imagination, symbolism, structure) may have played a role in the genesis of Bitcoin.